Uncovering Farmers’ Information Need through Kisan Call Centre Data Analytics of Haryana State (Indian Journal of Extension Education, 2024)
Data analytics in agriculture helps in precise decision-making, predict market trends, and address specific challenges faced by farmers resulting in sustainable agriculture. The present study investigates the information needs of farmers of Haryana by analysing 26.8 lakhs query calls made to the Kisan Call Centre from January 2009 to May 2024. The temporal and spatial analysis presents the evolution of call volumes over time along with their geographic distribution, further enabling district-wise targeted interventions. Calls are categorised based on crops and query type, providing a sense of the major crop-based challenges. Seasonal patterns in the queries and identification of critical periods are deciphered through month-wise analysis. Policymakers can formulate strategies according to the category, geographic, and chronological aspects of farmer inquiries. The research findings underscore the importance of data-driven insights in enhancing agricultural support systems, thus bettering the efficiency and effectiveness of the farming decisions in Haryana and beyond.